Determination of fatty acid profiles, cholesterol and D, E, K vitamin's content in Astacus leptodactylus caught from wild prior to reproduction period. Issue 1 (2nd January 2017) - Harlıoğlu, Ayşe Gül; Yılmaz, Ökkeş; Sarıgül, Halise
Abstract: In this study, fatty acids compositions, fat-soluble vitamins (D, E, and K) and cholesterol in the gonads, hepatopancreas, and abdomen muscle of male and female Astacus leptodactylus caught from wild were determined in their prior of reproduction period. The results showed that in female A. leptodactylus, compared with hepatopancreas, the ovaries contained a significantly high level of C16:0, C16:1n-7, C18:1n-9, C22:6n-3, the ratio of n-3 to n-6 ( p < 0.05). In females, the values of δ-tocopherol, α-tocopherol, K2 and D2 vitamins, and cholesterol obtained in ovaries were significantly higher than those of obtained in abdomen muscle and hepatopancreas ( p < 0.05). In male A. leptodactylus δ-tocopherol was found to be 1.91 μg/g in testes, which is significantly higher than that of abdomen muscle, hepatopancreas, and vasa deferentia ( p < 0.05). In conclusion, the findings of present study are especially constructive for both crayfish biologists and farmers for preparing broodstock diets for crayfish at reproduction units.